Papel do TREM-1 na imunopatogênese da leishmaniose visceral humana - Bomfim, Lays Gisele Santos (2022)
Visceral leishmaniasis (VL) is a parasitic, systemic, chronic and potentially fatal disease for humans. Mechanisms related to the dysregulation of the inflammatory response may be involved in the pathogenesis and prognosis of VL. Triggering Receptor Expressed on Myeloid Cells-1 (TREM-1) is a cell surface receptor constitutively expressed on neutrophils and monocytes subsets, with the function of regulating the inflammatory response. In VL, elevated serum levels of the soluble form of TREM-1 (sTREM-1) were observed in patients with severe VL and in vitro infection by L. infantum increased the expression and release of TREM-1 in neutrophils. Since the role of this receptor is still poorly understood in the context of VL, and the understanding of the mechanisms that lead to disease, cure and/or resistance are of great importance for the elucidation of immunopathogenic aspects, this study aimed to evaluate the participation of TREM-1 in the immunopathogenesis of human VL. For this, the in vitro release of sTREM-1 and the expression of surface activation markers (TREM-1, CD62L and CD182) in neutrophils exposed to L. infantum were evaluated by ELISA and flow cytometry, respectively. Then, the expression of these receptors in neutrophils of patients with VL was investigated at different times of treatment (D0, D7 and D30). Finally, we investigated the association of TREM-1 expression on the surface of neutrophils with clinical and laboratory parameters and serum levels of inflammatory mediators in patients with VL at different times of treatment. Our results demonstrate that exposure to L. infantum induces a greater release of sTREM-1 by neutrophils. In vitro exposure to the parasite decreases the activation phenotype with altered expression of TREM-1, CD62L and CD182 on the neutrophil surface. Neutrophils from VL patients, before treatment, have a lower expression of TREM-1 on the surface compared to healthy controls (HC). An increase in TREM-1 expression was observed seven days after the start of treatment, returning to similar levels found in CTR. TREM-1 expression was positively correlated with lymphocyte and erythrocyte count, and negatively correlated with spleen and liver size. Patients before treatment exhibited elevated levels of IL-4, IL-6, IL-12p70, IL-17A, IL-22, INF-γ e sTREM-1 compared to HC. TREM-1 expression was also negatively correlated with serum levels of IL-22. Whereas sTREM-1 was negatively correlated with TNF-α. In the analysis of hierarchical clustering was observed the formation of two large groups: sTREM-1, IL-22, IL-5 and IL-12p70, and other with IL-4, IL-17A, TNF- α, IL-6 and INF- γ. The results found corroborate the hypothesis that infection by L. infantum alters the expression of activation markers TREM-1, CD62L and CD182 on the surface of neutrophils, inducing the cells to an immature profile with a possible capacity to respond to an impaired stimulus. Furthermore, we found that TREM-1 expression is correlated with disease biomarkers, suggesting the participation of TREM-1 in VL immunopathogenesis.